Utopian Images and Narratives in Advertising: Dreams for Sale - Manca, Luigi; Manca, Alessandra; Pieper, Gail W. (Lexington Books, 2012)
The study of advertising and its treatment of utopian appeal enhance our understanding of consumer culture. By looking into the advertising page, we also look into consumers’ desires and the process by which these desires are reshaped and rechanneled through images and narratives created solely for the purpose of making a sale. Utopian Images and Narratives in Advertising: Dreams for Sale, edited by Luigi Manca, Alessandra Manca, and Gail W. Pieper, is a collection of essays which gather a host of academicians from a wide variety of disciplines including sociology, psychology, literature, fine arts, history, religious studies, communication, and media studies. Through their expansive disciplinary expertise, the contributors bring unique insights to the analysis of the advertising page. The collection’s cross-disciplinary investigation also examines gender images and narratives which, in the advertising page, are frequently associated with utopian fantasies. The analyses offered in Utopian Images and Narratives in Advertising will appeal to any scholar or student engaged in mass media, communication, and the effect of advertising and consumerism on individuals and cultures.